2012
DOI: 10.1017/s0022029911000902
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative effect of whey from cows’ milk varying in phyto-oestrogens in human breast and prostate cancer cells

Abstract: Intake of dietary phyto-oestrogens has received a great deal of attention owing to their potential influence on hormone-sensitive cancers such as breast and prostate cancer. Cows' milk contains phyto-oestrogens and the content varies according to the composition of the feed and the type and amount of legumes used. In this study we evaluated the proliferative effect of milk (whey) with different phyto-oestrogen content in human breast (MCF-7) and prostate cancer cells (PC-3). Milk was obtained from cows fed eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The bioactive compounds have been identified in this plant exhibit health benefits for humans, including antioxidative and antiinflammatory properties. [2,3] These bioactive compounds also occur in a normal diet, in a transformed form, via meat of livestock that feed on clover as well as milk and dairy products. [4] There are several reports on polyphenols with emphasis on isoflavonoid contents.…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive compounds have been identified in this plant exhibit health benefits for humans, including antioxidative and antiinflammatory properties. [2,3] These bioactive compounds also occur in a normal diet, in a transformed form, via meat of livestock that feed on clover as well as milk and dairy products. [4] There are several reports on polyphenols with emphasis on isoflavonoid contents.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that milk protein plays a key role in the development and modulation of prostate cancer cell proliferation [16,17,23]. Tate et al [16] reported that cow's milk stimulated the growth of prostate cancer cells (LNCaP) almost as much as digested whole milk.…”
Section: Discussionmentioning
confidence: 99%
“…Like our results, neither casein nor digested milk increased the growth of breast cancer cells (MCF-7). Nielsen et al [17] evaluated the effect of whey protein, a second fraction of milk protein, on prostate cancer cell (PC-3) growth. While whey had an anti-proliferative effect on breast cancer cells (MCF-7), this protein had a stimulatory effect on prostate cancer cell (PC-3) growth under the control of the estrogen concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations